Efektifitas Penggunaan Jenis Ekstender dan Dosis Madu Berbeda Terhadap Motilitas dan Viabilitas Sperma Ikan Nilem (Osteochilus vittatus) Setelah Penyimpanan - Dewi Wisudyanti Budi Hastuti; Riviani Riviani (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
This study aims to determine the effect of different types of extender and honey dosage on the percentage of motility and viability of nilem fish sperm after storage. This study used a completely randomized design (CRD) factorial pattern with a 2 x 3 pattern and 4 replications. The extender type factors consisted of egg yolk milk and coconut water, while the honey dosage factors were 0%, 3%, 6%, and 9%. The main parameters measured were sperm motility (%) and viability (seconds). Supporting parameters include odor, color, volume, pH, and viscosity. The data obtained were analyzed statistically at the 95% confidence level using analysis of variance (ANOVA). The data showed that all treatments, namely the type of extender, the dose of honey, and the interaction between them had the same effect on the motility and viability of the nilem fish sperm during storage.